Peran Wanita dalam Pembinaan Mental Agama Generasi Bangsa Masa Depan (Telaah Kritis Peran Ganda Perempuan Perspektif Islam) - Rohmah, Noer; Aziz, Nur Chotimah (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2018)
The history before arrivaling islam women or female didn’t have a decent dignity and also didn’t have value of dignity women were as merchandise that was worth trading and even as inheritance. The arrival of Islam by Muhammad SAW has brought the women into the better life and revolusion for women. Islam was extending the good position for women that are respected them by the revelation of Rosulullah SAW and it gave chance for them to build their career and also to excite the society. In women’s Islam it is likened to the pillar of the state, if the womens are good, the country will be good, and if it is damaged, the country will be damaged. Women have a set of rights and obligations that are closely related to the role they carry out, both roles in family, society and nation and state in realizing the best future generation of the nation.